Development of a CiFT Co-expression System for Functional Analysis of Genes in Citrus Flowers and Fruit - Endo, Tomoko; Shimada, Takehiko; Fujii, Hiroshi; Nishikawa, Fumie; Sugiyama, Aiko; Nakano, Michiharu; Shimizu, Tokurou; Kobayashi, Yasushi; Araki, Takashi; Pena, Leandro; Omura, Mitsuo (2017)
We have developed a CiFT co-expression system for the rapid evaluation of transgenic citrus flowers and fruit. In order to co-express a target gene and the CiFT gene, a CiFT co-expression vector was constructed by inserting the fragment containing a chimeric target gene into the binary vector harboring P35S::CiFT. This system was applied to metabolically engineer aroma components in trifoliate orange (Poncirus trifoliata L. Raf). In order to reduce the limonene level, a gene encoding limonene synthase (CitMTSE1) from satsuma mandarin (Citrus unshiu Marc.) was introduced into trifolliate orange in an anti-sense orientation with the CiFT co-expression vector. Transgenic plants flowered extremely early, and began to produce normal fruit within 2 years of Agrobacterium infection. Transcripts of transgenes were accumulated in reproductive tissues of transgenic plants, and endogenous transcripts for limonene synthase were reduced. The ratio of limonene to other monoterpenes was significantly decreased in flowers and fruit of transgenic plants. These results clearly indicated that the CiFT co-expression system is a useful tool for the functional analysis of genes in citrus flowers and fruit. Such analyses are important for several applications, including the metabolic engineering of aroma components in citrus.